2013
DOI: 10.1007/s00170-013-4902-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy density analysis on single tracks formed by selective laser melting with CoCrMo powder material

Abstract: Selective laser melting (SLM) is an advanced manufacturing technology based on layer by layer building to produce solid parts from metallic powder (Kruth et al., CIRP Ann Manuf Technol 56:730-760, 2007). Commercial SLM machines are configured to use specific parameters to process different metallic powder grades. This paper proposes a methodology that makes it possible to analyze the effect of energy density on the formation of single tracks from CoCrMo powder, using a noncommercial machine to select process p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(55 citation statements)
references
References 21 publications
2
52
0
1
Order By: Relevance
“…To establish the optimal process parameters, an objective function (F) was determined [12,13]. This considers the relationship between the melting zone area (A1) and the penetration zone (A2), as follows: F = A1/A2 (Equation (2)), where A1 = (W1 + W3/2) × H1 (Equation (3)), in which H1 and W1 are the height and width, respectively, of the upper part of the line.…”
Section: Single-line Formation Testmentioning
confidence: 99%
See 3 more Smart Citations
“…To establish the optimal process parameters, an objective function (F) was determined [12,13]. This considers the relationship between the melting zone area (A1) and the penetration zone (A2), as follows: F = A1/A2 (Equation (2)), where A1 = (W1 + W3/2) × H1 (Equation (3)), in which H1 and W1 are the height and width, respectively, of the upper part of the line.…”
Section: Single-line Formation Testmentioning
confidence: 99%
“…The Ra of each specimen was recorded using the average value of five readings. To establish the optimal process parameters, an objective function (F) was determined [12,13]. This considers the relationship between the melting zone area (A 1 ) and the penetration zone (A 2 ), as follows:…”
Section: Multi-layer Formation Testmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that the selection of a layer thickness is influenced by two main factors: the powder particle size distribution and the extent of shrinkage during the process. Ciurana et al (2013) used a tilted platform to investigate the effect of layer thickness, laser power, and scan speed, simultaneously, on CoCrMo single tracks and defined the threshold for the energy density to avoid single track defects. There are fewer studies with attention focusing on Al alloys.…”
Section: Introductionmentioning
confidence: 99%